National Security Policies of Nigeria and Benin Republic as Strategies for Curbing Cross-border Crimes - Adenipekun, Lawerence Olu (African Journal of Stability and Development (AJSD), 2022)
This study interrogates the constantly changing national security policies of Nigeria and Benin Republic in response to the cross-border security threats that are currently ravaging the two West African countries. The common focus in extant literature is on the diverse transnational organised crimes, with little or no attention paid to the manner in which the security threats have substantially shaped the national security policies of the two states. The study is guided by critical human security theory. Data was collected from primary sources; 13 interviews were conducted in Nigeria and Benin Republic, which were complimented by direct observations at the Nigeria-Benin borders. Some data were also derived from secondary sources, and the analysis of data generated was essentially qualitative, using descriptive and content analyses. Findings show that the security policies of both countries are encapsulated in an array of different documents and that they are, essentially, reactions to the constantly evolving security threats. The study calls for the harmonisation of border security policies of the two neighbouring countries in order to successfully rein in on cross-border criminal cartels.